The Effect of The Insecticide Hulk on Some Genetic Characteristics of The Whitefly and The Cucumber Plant That Parasitizes It - Abd, Rania Ghasan; AlSugmiany, Rafea Zaidan Mikhlif (Journal for Research in Applied Sciences and Biotechnology, 2024)
Background: Whitefly, Bemisia tabaci is one of the major injurious sucking pests in tropical and subtropical regions. The effect of the insecticide Hulk, which is used to kill the whitefly, was revealed, and its effect on some of its genes and the genes of the cucumber plant that parasitizes it, was revealed. Materials and Methods: The current study was conducted in Kirkuk Governorate. DNA was extracted from whiteflies treated with Hulk pesticides and not treated with pesticides as a control, and DNA was also extracted from cucumber leaves treated with the Hulk pesticide and not treated with the pesticide as a control in order to compare them. detecting the specific primer of gene 28s in the whitefly Bemisia tabaci and Matk gene in the plant Cucumis sativus. Three treatments of each pesticide at three concentrations (25% a quarter lethal, 50% half lethal, 100% lethal). Results: The research found that 25% of the pesticide Halk killed 20% of the insects, 50% killed 40%, and 100% killed 70% within 24 hours. Pesticide Hulk found that cucumber plant mutations in the Matk gene and gene 28s had the best insecticidal effects against whitefly Bemisa tabaci. Conclusions: Overall, results suggest that ethanolic DNA extracts pesticide Hulk is the occurrence of mutations in the Matk gene in the plant Cucumis sativus and gene 28s in the whitefly Bemisia tabaci showed the highest insecticidal effects on whitefly Bemisa tabaci.